Vaccine hesitancy: challenges and solutions - Karafillakis, Emilie (Henry Stewart Talks, 2023)
Vaccine hesitancy, Vaccine confidence, Decision making processes, Trust asymmetry, Misinformation, COVID-19, Polarization, politics and populism, Beyond the knowledge-deficit model, Communication techniques, Motivational interviewing